STYDY OF VALUE SYSTEM AND ETHNIC CONSCIOUSNESS OF KAZAKH ORPHANAGE CHILDREN - Syrgakbayeva A. S.; Berdibayeva S. K.; Mayemirov A. M.; Kukubayeva А. H.; Konrad Reschke (Scientific Journal of Pedagogy and Economics, 2019)
The aims of research is to investigate value system and ethnic consciousness of orphan children in modern Kazakhstan. So we found that of ethnic consciousness still develop and it’s in low level in Kazakh orphanage children and there is significant difference in value system between Kazakh orphanage children and children who have a family.